The Meaning of Being a School Counselor (Phenomenology Studies on Fresh Graduate) - Irawan, Andi Wahyu (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
This study aims to determine the meaning of being a guidance and counseling teacher at Samarinda Senior High School. This research used a qualitative approach with phenomenological methods. The research subjects were selected using purposive sampling criteria with fresh graduates and serving no more than one year, honorary status, not more than 25 years old, and working in a high school in Samarinda. Data collection techniques used in-depth interviews and were analyzed using Interpretative Phenomenological Analysis (IPA) techniques. The analysis technique seeks to find the meanings of being a School Counselor. The results showed two main themes. Namely, the School Counselor is interpreted as a calling and to enjoy comfort. The sub-theme of vocation is not profit-oriented, realizing the future of students, and religious beliefs. The sub-theme of enjoying comfort is feeling comfortable when students are helped, enjoying being parents for students, and getting life lessons. Suggestions from this study are expected to be a reference in helping counseling teachers in the process of interpreting their work through positive environmental conditioning to increase their productivity at work